The Influence of Non-Structural Mitigation Education on Understanding Community Preparedness for Flood Disaster in Sumberrejo District - Andreinata Indrawijaya; Axel Prasetya Adoe; Moh Sofyan Sofyan; Rizal Abdi Utomo; Mohamad Ferdaus Noor Aulady (Faculty of Civil Engeneering and Planning - ITATS, 2023)
Indonesia is a developing country that is prone to disasters, especially floods. Based on data from DIBI, recorded from 2013 to 2018, Bojonegoro Regency has experienced 299 disaster events out of 5 types of disasters with floods being the most frequent. One of the affected areas is the Sumberrejo District. Non-structural mitigation planning is an essential part of efforts to reduce disaster risk, therefore this research focuses on providing education on appropriate non-structural mitigation. The purpose of this study is to analyze the influence of non-structural mitigation education on understanding community preparedness for flood disasters in Sumberrejo district. The activity was carried out in the form of giving closed questionnaires and giving educational socialization using the oral explanation method and brochures, which contained education regarding introduction to a sustainable environment, and flood non-structural mitigation. Afterward, a final questionnaire was given with the results obtained: the knowledge of respondents regarding the importance of environmental sustainability and non-structural flood disaster mitigation efforts has increased, where as many as 39 respondents (86.7% of respondents) out of a total of 45 respondents experienced an increase in post-test scores due to the education carried out in this study and 71.1% of respondents were able to answer more than 70% of the post-test questions correctly. The improvement of the total value of the post-test average score (5.93) compared to the pre-test score (7.44) increased by 1.51, which showed that the respondents' understanding of non-structural mitigation for flood disasters increased through the holding of education that had been carried out by this study.